Isolation and identification of two causal agents associated with root rot of Scutellaria baicalensis - Lin He; Qianci Chen; Pingping Sun; Lei Zhang; Honghong Jiao; Hongmei Cui; Yuan Yuan; Zhengnan Li (Physiological and Molecular Plant Pathology, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Effects of ecological restoration on soil organic carbon in degraded sloping cropland: An 8-year resampling study - Meiying Wang; Honghong Lin; Xingwu Duan (Agriculture, Ecosystems & Environment, 2026)

Spatial mapping of metabolite distribution in Dendrobium officinale stems across different ages by MALDI-MSI - Junru Huang; Yasmin Khan; Liujuan Cheng; Silin Zhang; Weixiang Xiao; Xu Sun; Lin Liu; Honghong Fan (Food Research International, 2025)

Rapid and efficient removal of aqueous perfluorooctane sulfonate at environmentally relevant concentrations using photoregenerable modified biochar - Dongjiao Lin; Honghong Lyu; Yingjie Liu; Yanyan Gong (Chemical Engineering Journal, 2025)

Catalytic oxidation of volatile organic compounds over supported noble metal and single atom catalysts: A review - Honghong Zhang; Zhiwei Wang; Hongxia Lin; Yuxi Liu; Hongxing Dai; Jiguang Deng (Journal of Environmental Sciences, 2025)

Salidroside alleviates doxorubicin-induced hepatotoxicity via Sestrin2/AMPK-mediated pyroptotic inhibition - Nan Wang; Zhengshan Gao; Honghong Zhan; Lin Jing; Fancheng Meng; Min Chen (Food and Chemical Toxicology, 2025)

Mycobacterium marinum mediates regulation of prostaglandin E2 expression on host immune response through cyclooxygenase pathway - Dongzi Lin; Bingyao Lin; Xuezhi Wang; Cheng Xu; Liyi Mo; Yanwen Luo; Honghong Tian; Lei Zhou; Zhenhua Chen (Molecular Biology Reports, 2024)

Predicting frost heave in soil-water systems using the generalized regression neural network optimized with particle swarm optimization algorithm - Honghong Cai; Chong Wang; Ziqiang Ma; Fanshuo Meng; Zhikun Lin; Junping Ren; Shuangyang Li (Cold Regions Science and Technology, 2024)

Functional characterization of terpene synthases SmTPS1 involved in floral scent formation in Salvia miltiorrhiza - Xiaohong Li; Lin Liu; Jin Chu; Guo Wei; Jiaxue Li; Xu Sun; Honghong Fan (Phytochemistry, 2024)

Soil inorganic carbon stock and its changes across the Tibetan Plateau during the 1980s–2020s - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Hua Zheng; Yun Xie; Li Rong; Haijuan Zhao; Shengzhao Wei (Global and Planetary Change, 2024)

Zeolite structure descriptor for guiding the synthesis of efficient titanosilicalites through matching Ti sites and framework topologies for 1-Hexene epoxidation - Xuliang Deng; Dong Lin; Yang Xu; Xiang Feng; De Chen; Chaohe Yang; Honghong Shan (Chemical Engineering Journal, 2024)

Acid-assisted ultrasonic preparation of nitrogen-doped MXene quantum dots for the efficient fluorescence “off-on-off” detection of Zn(II) in water and oxalic acid in vegetables - Jinwen Yang; Linlin Chen; Jie Qi; Feili Luo; Lin Li; Honghong Wu; Feifei Cao; Jiangjiang Gu (Food Chemistry, 2024)

Activation of indigenous denitrifying bacteria and enhanced nitrogen removal via artificial mixing in a drinking water reservoir: Insights into gene abundance, community structure, and co-existence model - Shangye Yang; Tinglin Huang; Haihan Zhang; Honghong Guo; Ruzhu Hu; Zishen Lin; Yanqing Li; Ya Cheng (Environmental Research, 2023)

Dexmedetomidine Regulates Autophagy via the AMPK/mTOR Pathway to Improve SH-SY5Y-APP Cell Damage Induced by High Glucose - Pinzhong Chen; Xiaohui Chen; Honghong Zhang; Jianghu Chen; Mingxue Lin; Haitao Qian; Fei Gao; Yisheng Chen; Cansheng Gong; Xiaochun Zheng; Ting Zheng (NeuroMolecular Medicine, 2023)

Responses of soil water-holding capacity to environmental changes in alpine ecosystems across the southern Tibetan Plateau in the past 35–40 years - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Li Rong; Jiangcheng Huang (CATENA, 2023)

Single-atom Mn anchored on N-doped graphene oxide for efficient adsorption-photocatalytic degradation of sulfanilamide in water: Electronic interaction and mineralization pathway - Honghong Lyu; Pin Li; Jingchun Tang; Weixin Zou; Pengfei Wang; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

The genesis of Guanting Pb–Zn deposits in the Jianshui area, Yunnan Province, SW China: Constraints from geochronology, S isotopes and trace elements - Xiaoli Shen; Honghong Lin; Baolin Zhang; Qingxiang Du (Mineralogy and Petrology, 2022)

Amitriptyline Protects Against Lidocaine-induced Neurotoxicity in SH-SY5Y Cells via Inhibition of BDNF-mediated Autophagy - Honghong Zhang; Xiaohui Chen; Ting Zheng; Mingxue Lin; Pinzhong Chen; Yanling Liao; Cansheng Gong; Fei Gao; Xiaochun Zheng (Neurotoxicity Research, 2021)

Correction to: IL-17A Induces MIP-1α Expression in Primary Astrocytes Via Src/MAPK/PI3K/NF-kB Pathways: Implications for Multiple Sclerosis - Hongwei Yi; Ying Bai; Xinjian Zhu; Lin Lin; Lei Zhao; Xiaodong Wu; Shilpa Buch; Longxin Wang; Jie Chao; Honghong Yao (Journal of Neuroimmune Pharmacology, 2021)

Duplex real-time quantitative PCR for simultaneous detection and quantification of Pratylenchus neglectus and P. thornei - Borong Lin; Ye Tao; Honghong Wang; Jinling Liao; Kan Zhuo (European Journal of Plant Pathology, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

Effects of reciprocal hybridization on cadmium accumulation in F1 hybrids of two Solanum photeinocarpum ecotypes - Lijin Lin; Caifang Wu; Jin Wang; Ming’an Liao; Daiyu Yang; Honghong Deng; Xiulan Lv; Hui Xia; Dong Liang; Qunxian Deng (Environmental Science and Pollution Research, 2020)

Methylmalonate‐semialdehyde dehydrogenase mediated metabolite homeostasis essentially regulate conidiation, polarized germination and pathogenesis in Magnaporthe oryzae - Justice Norvienyeku; Zhenhui Zhong; Lili Lin; Xie Dang; Meilian Chen; Xiaolian Lin; Honghong Zhang; Wilfred M. Anjago; Lianyu Lin; Waheed Abdul; Zonghua Wang (Environmental Microbiology, 2017)
Summary Plants generate multitude of aldehydes under abiotic and biotic stress conditions. Ample demonstrations have shown that rice‐derived aldehydes enhance the resistance of rice against the rice‐blast fungus Magnaporthe oryzae . However, how the fungal pathogen nullifies the inhibitory effects of host aldehydes to establish compatible interaction remains unknown. Here we identified and evaluated the in vivo transcriptional activities of M. oryzae aldehyde dehydrogenase (ALDH) genes. Transcriptional analysis of M. oryzae ALDH genes revealed that the acetylating enzyme Methylmalonate‐Semialdehyde Dehydrogenase (MoMsdh/MoMmsdh) elevated activities during host invasion and colonization of the fungus. We further examined the pathophysiological importance of MoMSDH by deploying integrated functional genetics, and biochemical approaches. MoMSDH deletion mutant Δ Momsdh exhibited germination defect, hyper‐branching of germ tube and failed to form appressoria on hydrophobic and hydrophilic surface. The MoMSDH disruption caused accumulation of small branch‐chain amino acids, pyridoxine and AMP/cAMP in the Δ Momsdh mutant and altered Spitzenkörper organization in the conidia. We concluded that MoMSDH contribute significantly to the pathogenesis of M. oryzae by regulating the mobilization of Spitzenkörper during germ tube morphogenesis, appressoria formation by acting as metabolic switch regulating small branch‐chain amino acids, inositol, pyridoxine and AMP/cAMP homeostasis.

Cloning and characterization of DoMYC2 from Dendrobium officinale - Yanfang Zhu; Cancan Meng; Liqin Zhu; Dahui Li; Qing Jin; Cheng Song; Yongping Cai; Honghong Fan; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Loop-mediated isothermal amplification based on the mitochondrial COI region to detect Pratylenchus zeae - Xingtong Liu; Honghong Wang; Borong Lin; Ye Tao; Kan Zhuo; Jinling Liao (European Journal of Plant Pathology, 2017)

Molecular cloning and expression of 1-deoxy-d-xylulose-5-phosphate synthase and 1-deoxy-d-xylulose-5-phosphate reductoisomerase in Dendrobium officinale - Honghong Fan; Qiuju Wu; Xiang Wang; Linsong Wu; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

The caspase-8 shRNA-modified mesenchymal stem cells improve the function of infarcted heart - Yeyou Liang; Qiuxiong Lin; Jiening Zhu; Xiaohong Li; Yongheng Fu; Xiao Zou; Xiaoying Liu; Honghong Tan; Chunyu Deng; Xiyong Yu; Zhixin Shan; Weiwei Yuan (Molecular and Cellular Biochemistry, 2014)

IL-17A Induces MIP-1α Expression in Primary Astrocytes via Src/MAPK/PI3K/NF-kB Pathways: Implications for Multiple Sclerosis - Hongwei Yi; Ying Bai; Xinjian Zhu; Lin lin; Lei Zhao; Xiaodong Wu; Shilpa Buch; Longxin Wang; Jie Chao; Honghong Yao (Journal of Neuroimmune Pharmacology, 2014)

Variations of DNA methylation and genes expression for brown fiber during its development process - Zhenpeng Li; Tingchun Li; Honghong Fan; Ning Guo; Xu Sun; Yongping Cai; Yi Lin (Acta Physiologiae Plantarum, 2014)

Effects of exogenous nitric oxide on antioxidation and DNA methylation of Dendrobium huoshanense grown under drought stress - Honghong Fan; Tingchun Li; Lei Guan; Zhengpeng Li; Ning Guo; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

The accumulation of pigment in fiber related to proanthocyanidins synthesis for brown cotton - Tingchun Li; Honghong Fan; Zhengpeng Li; Jun Wei; Yi Lin; Yongping Cai (Acta Physiologiae Plantarum, 2012)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Recovery of transgenic orchid plants with hygromycin selection by particle bombardment to protocorms - Zhihua Yu; Minyong Chen; Lin Nie; Huafei Lu; Xiaotian Ming; Honghong Zheng; Li-Jia Qu; Zhangliang Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 1999)